Pengaruh Motivasi Intrinsik, Kompensasi Financial dan Iklim Organisasi dengan Organizational Citizenship Behavior (OCB) Karyawan Sebagai Variabel Intervening dan Dampaknya terhadap Kinerja di PT. Central Mega Kencana - Bella Puspita Audina; R Dimas Praditya; Suryono Efendi (Serat Acitya, 2022)
This study aims to analyze how much the influence of Intrinsic Motivation, Financial Compensation and Organizational Climate on OCB and its impact on employee performance at PT. Central Mega Kencana. This study uses a survey method by distributing questionnaires to employees at PT. Central Mega Kencana as the respondent. Quantitative research methods with Structural Equation Modeling (SEM)analysis techniques with the application of AMOS version 22. The samples in this study were 145 respondents. The results showed that Intrinsic Motivation, Financial Compensation and Organizational Climate directly had a positive effect on employee performance. and OCB has a positive and significant effect on the performance of employees at PT. Central Mega Kencana.